Biología del salivazo Prosapia simulans (Homoptera: Cercopidae), nueva plaga de gramíneas cultivadas en Colombia - Rodríguez Chalarca, Jairo; Castro, U.; Morales Rodriguez, A.; Peck, DC (2003)
The first detection of the spittlebug Prosapia simulans (Walker) (Homoptera; Cercopidae) for Colombia in 1999 was a warning for ranchers and sugar cane growers in the Cauca Valley, where it already has achieved economic levels in Brachiaria. Despite its importance in pastures and cane in Central America, little is known about its biology. In order to obtain the foundation necessary to advance in its management, morphological measurements were used to recognize the life stages. To quantify the life cycle, observations were made of eggs in petri dishes under incubation, and the nymphs and adults on potted host plants. To establish oviposition sites, eggs were recovered from groups of females maintained in pots with different substrates. As with other species of spittlebugs, the eggs of P. simulans passed through four morphologically distinguishable developmental stages, the nymphs passed through five instars, and the adults showed sexual dimorphism. The duration of the egg stage was 18 ± 1,3 days, the nymphs 45,6 ± 5,4 days, and the mean longevity of the adults was 16,5 days, for a total life cycle of 71,9 days. An additional study confirmed a high incidence of diapause in eggs from the field (69,8% in the period of January-May 2000) where egg eclosion was extended up to 128 days. Females exhibited a preference for the stem as an oviposition site with 82,7% of the eggs recovered. In contrast with other species of the spittlebug complex in Colombia, P. simulans has a long life cycle and prefers the stem over soil as oviposition substrate. So far, the presence of P. simulans is limited to four localities of the Cauca Valle.